Analisis Perpajakan terhadap Insentif PPH Final atas Kepatuhan Wajib Pajak UMKM di Pamekasan - Fitrianti, Rani Nur; Rahayu, Runik Puji; Rohmaniyah, Rohmaniyah; Alfian, Nurul (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The aim of this research is to find out how understanding of taxation and final PPh incentives affects taxpayer compliance. The research method uses a quantitative descriptive approach. The population in this research is corporate MSME taxpayers who take advantage of the final income tax incentives. The sampling technique used is non-probability sampling, namely purposive sampling. The type of data used in this research is quantitative data with a descriptive approach, namely in the form of primary data and secondary data. Based on the previous results and discussion, it can be concluded that: Results Based on the first hypothesis test (H1) in this study, the tax understanding variable shows a significant value smaller than 0.05, namely 0.000 and the second hypothesis test (H2) in this study, the tax incentive variable final income shows a significant value smaller than 0.05, namely 0.000.